Infection of Cattle with a Bovine Herpesvirus 1 Strain That Contains a Mutation in the Latency-Related Gene Leads to Increased Apoptosis in Trigeminal Ganglia during the Transition from Acute Infection to Latency - Lovato, Luciane (American Society for Microbiology, 2003)
Bovine herpesvirus 1 (BHV-1) is an important pathogen of cattle and infection is usually initiated via the ocular or nasal cavity. After acute infection, the primary site for BHV-1 latency is sensory neurons in the trigeminal ganglia (TG). Reactivation from latency occurs sporadically, resulting in virus shedding and transmission to uninfected cattle. The only abundant viral transcript expressed during latency is the latency-related (LR) RNA. An LR mutant was constructed by inserting three stop codons near the beginning of the LR RNA. This mutant grows to wild-type (wt) efficiency in bovine kidney cells and in the nasal cavity of acutely infected calves. However, shedding of infectious virus from the eye and TG was dramatically reduced in calves infected with the LR mutant. Calves latently infected with the LR mutant do not reactivate after dexamethasone treatment. In contrast, all calves latently infected with wt BHV-1 or the LR rescued mutant reactivate from latency after dexamethasone treatment. In the present study, we compared the frequency of apoptosis in calves infected with the LR mutant to calves infected with wt BHV-1 because LR gene products inhibit apoptosis in transiently transfected cells. A sensitive TUNEL (terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling) assay and an antibody that detects cleaved caspase-3 were used to identify apoptotic cells in TG. Both assays demonstrated that calves infected with the LR mutant for 14 days had higher levels of apoptosis in TG compared to calves infected with wt BHV-1 or to mock-infected calves. Viral gene expression, except for the LR gene, is extinguished by 14 days after infection, and thus this time frame is operationally defined as the establishment of latency. Real-time PCR analysis indicated that lower levels of viral DNA were present in the TG of calves infected with the LR mutant throughout acute infection. Taken together, these results suggest that the antiapoptotic properties of the LR gene play an important role during the establishment of latency.